SOCIOPOLITICAL, CEREMONIAL, AND ECONOMIC ASPECTS OF GAMBLING IN ANCIENT NORTH AMERICA: A CASE STUDY OF CHACO CANYON. Issue 1 (29th September 2017) - Weiner, Robert S.
Abstract : This paper builds upon DeBoer's (2001 ) assertion that models of ancient North American cultural systems can be enriched by incorporating gambling as a dynamic and productive social practice using the case study of the Ancient Puebloan center of Chaco Canyon (ca. AD 800–1180). A review of Native North American, Pueblo, and worldwide ethnography reveals gambling's multidimensionality as a social, economic, and ceremonial technology in contrast to its recreational associations in contemporary Western society. I propose that gambling was one mechanism through which leaders in precontact North America—and, specifically, at Chaco Canyon—integrated diverse communities, facilitated trade, accumulated material wealth, perpetuated religious ideology, and established social inequality. I present evidence of gambling at Chaco Canyon in the form of 471 gaming artifacts currently held in museum collections in addition to oral traditions of descendant Native cultures that describe extensive gambling in Chacoan society. Abstract : Este trabajo se basa en la afirmación de DeBoer (2001) que podemos enriquecer nuestros modelos de los antiguos sistemas culturales norteamericanos si tomamos en cuenta el juego como práctica social dinámica y productiva, utilizando como estudio de caso el centro Pueblo prehispánico del Cañón del Chaco (ca. 800–1180 dC). Un repaso de la etnografía indígena norteamericana, Pueblo, y mundial revela las múltiples dimensiones de los juegos de azar como una tecnología social, económica y ceremonial que contrasta con sus asociaciones recreativas en la sociedad occidental contemporánea. Propongo que el juego era un mecanismo a través del cual los líderes en Norteamérica precolombina—y, específicamente, en el Cañón del Chaco—integraron diversas comunidades, facilitaron el comercio, acumularon riqueza material, perpetuaron la ideología religiosa y establecieron la desigualdad social. Presento evidencia del juego en el Cañón del Chaco en la forma de 471 artefactos para el juego actualmente guardados en colecciones de museos, además de las tradiciones orales de las culturas indígenas descendientes que describen la frecuencia del juego de azar en sociedad precolombina del Cañón del Chaco.